Meaning Accounting from a Travel Trader's Point of View - Anastasya Dyah Lestari Putri; Ayudia Sokarina (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to reveal the meaning of accounting from the perspective of traveling traders. This research uses a qualitative research method with a phenomenological approach. Data collection techniques use observation, interviews and documentation. The informants in this research are traveling traders who carry out their business in the Karang Baru neighborhood, Kebun Sari Village, Ampenan District. The data analysis stages consist of Noema, Epoche, Noesis, Intentional Analysis, and Eidetic Reduction. The research results showed that the informants did not keep financial records of their businesses. The two informants only used their minds to determine the profit or loss of their business. Researchers found, based on the in-depth awareness of traveling traders, profits were interpreted as economic and non-economic. The economic meaning is savings or reserves used to meet the family's daily economic needs and as business capital. Meanwhile, the non-economic meaning is a transcendent meaning in the form of inner satisfaction and gratitude for the blessings of sustenance given by God in their efforts. This research provides an explanation of the recording accounting practices used by traveling traders and explains the meaning of profit from the perspective of traveling traders.